Antibacterial effect and impact on caries activity of nanosilver fluoride and silver diamine fluoride in dentin caries of primary teeth: a randomized controlled clinical trial - Nour Ammar; Magda M. El-Tekeya; Sara Essa; Marwa M. Essawy; Dalia M. Talaat (BMC, 2022)
Abstract Background The use of silver diamine fluoride (SDF) in caries treatment in children has increased despite the disadvantage of causing tooth discoloration. Nanosilver fluoride (NSF) is a possible alternative. This study aimed to assess the antibacterial effect of NSF and SDF and their impact on the activity of dentin caries in primary teeth. Methods Synthesis and characterization of the physical and biological properties of NSF were conducted. Fifty children aged 4-6 years with dentin caries (active caries corresponding to ICDAS code 5) in deciduous teeth were randomly assigned to treatment by NSF or SDF. Baseline assessment of Streptococcus mutans (S. mutans) and lactobacilli counts as CFU/mL in caries lesions was done, followed by the application of the agents. After one month, microbiological samples were recollected, and lesion activity was reassessed. Groups were compared using Mann-Whitney and Chi-Square tests, while intragroup comparisons were done using Wilcoxon and McNemar tests. Multilevel logistic regression analysis was used to assess the effect of different variables on the outcomes. Results There were 130 teeth in 50 children; mean ± SD age = 4.75 ± 0.76 years, 63% were posterior teeth. At the one-month follow-up appointment, both groups showed a significant decrease from baseline bacterial counts. There was a significant difference in the reduction of S. mutans between NSF and SDF (21.3% and 10.5%, respectively, p = 0.002), while not in lactobacilli (13.9% and 6.0%, respectively, p = 0.094). In both groups, there was a significant reduction in the number of active caries from baseline (p < 0.0001) with no significant difference between groups (percentage inactive = 64.4% and 63.4%, p = 0.903). Multilevel regression revealed non-significant differences in S. mutans and lactobacilli counts (AOR 1.281, p = 0.737 and 1.888, p = 0.341, respectively), and in the number of inactive lesions (AOR 1.355, p = 0.731) between groups. Conclusion The short-term antibacterial efficacy of NSF was similar to that of SDF. In both groups there was a significant reduction of S. mutans and lactobacilli counts in active dentin caries, and two-thirds of the lesions became inactive with no differences between the two interventions. Further research is needed to investigate the long-term efficacy of NSF and its suitability for clinical use in caries management. Trial registration: This trial was prospectively registered on the clinicaltrials.gov registry with ID: NCT05221749 on 03/02/2022.